2001
DOI: 10.4141/s00-072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light on birnessite catalysis of the Maillard reaction and its implication in humification

Abstract: Jokic, A., Frenkel, A. I. and Huang, P. M. 2001. Effect of light on birnessite catalysis of the Maillard reaction and its implication in humification. Can. J. Soil Sci. 81: 277-283. The Maillard reaction between carbohydrates and nitrogenous compounds originally investigated in 1912 has subsequently been proposed as a possible pathway for the formation of humic substances in natural environments. However, the role of mineral catalysis of the Maillard reaction is little understood and the promoting effect of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Because of MnO 6 octahedral, the FTIR spectra of original and CIP-absorbed birnessite had a strong absorption peak at about 520 cm −1 . A broad weak and a strong broad peaks appeared in 1624 and 3431 cm −1 with the former attributed to less ordered water and the latter to OH, H 2 O adsorbed on birnessite [26]. The other explanation of these phenomena was the bending mode of H 2 O and the stretching mode of the OH groups.…”
Section: Ftir Analysesmentioning
confidence: 97%
“…Because of MnO 6 octahedral, the FTIR spectra of original and CIP-absorbed birnessite had a strong absorption peak at about 520 cm −1 . A broad weak and a strong broad peaks appeared in 1624 and 3431 cm −1 with the former attributed to less ordered water and the latter to OH, H 2 O adsorbed on birnessite [26]. The other explanation of these phenomena was the bending mode of H 2 O and the stretching mode of the OH groups.…”
Section: Ftir Analysesmentioning
confidence: 97%
“…For raw birnessite, a broad weak peak and a broad strong peak were located at 1,624 and 3,431 cm -1 with the former assigned to less ordered water and the latter to -OH, H 2 O adsorbed on birnessite (Jokic et al 2001). Separately, the broad band at 3,280-3,400 cm -1 was assigned to the stretching mode of OH groups, while the band at 1,610 cm -1 was assigned to the bending mode of H 2 O (White et al 2009).…”
Section: Ftir Analysesmentioning
confidence: 98%
“…This reaction is kinetically sluggish under ambient temperatures (Jokic et al, 2001c ), but the presence of birnessite signifi cantly catalyzes the reaction by decreasing the activation energy required. Jokic et al (2001a) investigated the effect of light on birnessite catalysis of the Maillard reaction, and they showed that the reaction is promoted by light but also readily occurs in the absence of light. This means that the reaction could readily occur in the subsoil in the presence of a mineral catalyst such as birnessite.…”
Section: Oxides Oxyhydroxides and Short -Range Ordered Mineralsmentioning
confidence: 99%